Lecturers’ Strategies in Teaching Toefl to Non-English Deparment Students at State College for Islamic Studies (STAIN) Curup - Leffi Noviyenty (Ahmad Dahlan Journal of English Studies, 2019)
AbstractThe objectives of this research are to find out the strategies, the reason the lecturers use the strategies, the way they implement the strategies and the problems they faced in implementing the strategies.  The data is collected though deep interview and observation.    The findings shows that the strategies used are: Teaching the usage not the rules, helping the students with the four skills, teaching the students the strategies in doing the TOEFL, using appropriate material, note taking, doing the preparation and using students’ psychic abilities.  The reason the English lecturers use the strategies are to build the students self confident, to train the students using the time effectively, to minimize tthe students weaknesses and strengthen their power in order to get good score, to make the students find their own strategies in doing the test as fast as they can, and to train the students do self correction by note taking. While the implementation of  strategies perform in variety ways.  Some problems are also found such as the students have low motivation on TOEFL, very limited background on TOEFL, rarely read English text outclass and the students have bad score in English Subject.